Application of time‐resolved angiography with stochastic trajectories (twist)‐dixon in dynamic contrast‐enhanced (dce) breast mri. Issue 5 (5th September 2013) - Le, Yuan; Kipfer, Hal; Majidi, Shadie; Holz, Stephanie; Dale, Brian; Geppert, Christian; Kroeker, Randall; Lin, Chen
Abstract : Purpose: To evaluate a magnetic resonance imaging (MRI) technique that integrates time‐resolved angiography with stochastic trajectories (TWIST) view sharing and Dixon for a breast dynamic contrast‐enhanced (DCE)‐MRI application. Materials and Methods: Simulation study: K ‐space data at six timepoints (1 pre‐, 5 postcontrast) were generated by performing Fourier transform on a digital "phantom" with 3–9 mm enhancing lesions and three types of enhancement curves (persistent, plateau, washout). Images were reconstructed with and without TWIST. Clinical study: Six TWIST‐Dixon image sets (one pre‐, five postcontrast) were acquired in 18 patients on a 3T scanner, followed by one conventional image set. The last TWIST‐Dixon and the conventional images were scored for seven criteria: perceived signal‐to‐noise ratio (P.SNR), visualization of anatomy, fat suppression (FS) accuracy, FS uniformity, ghosting artifact, edge ringing artifact, and overall image quality (IQ). Results: Simulation study: With proper TWIST parameters (pA ≥33%, pB ≥50%), the enhancement underestimation was 5% or less for tumor size ≥5 mm. Clinical study: TWIST‐Dixon images have significantly better scores in all criteria except for ghosting artifacts, where the difference was not significant. Conclusion: With proper parameters, TWIST‐Dixon provides higher perceived SNR, more accurate fat suppression, and better overall image quality for breast DCE‐MRI without sacrificing accuracy in the enhancement estimation. J. Magn. Reson. Imaging 2013;38:1033–1042. © 2013 Wiley Periodicals, Inc.